Peningkatan Pengetahuan Siswa Sekolah Dasar Tentang Bahaya Rokok dan Vaping Melalui Program Edukasi Kesehatan - Nurul Maulidiyah (Jurnal Pengabdian Kepada Masyarakat, 2026)
This community service activity aims to improve the knowledge of 5th and 6th grade students at SDN 2 Marga Agung regarding the dangers of smoking and vaping. The low level of student understanding regarding the harmful substances contained in cigarettes and the risk of becoming a passive smoker was the background for the implementation of this educational program. The activity was carried out on October 17, 2025, using interactive counseling methods, visual media, and question-and-answer sessions. Evaluation used pre-test and post-test administered to 98 students on questions 11–15 covering knowledge of nicotine, lung damage from cigarette smoke, passive smoking, and diseases caused by smoking. Results showed significant improvement in all indicators. Understanding of passive smoking increased most sharply from 61.2% to 87.8%. Overall, the average student score increased from 79.5 in the pre-test to 86.8 in the post-test. This program proved effective in improving students' health literacy regarding the dangers of smoking and vaping.